AN OVERVIEW OF THE BRITISH ATTEMPT TO EXPLORE THE WEST AFRICAN INTERIOR, WITH PARTICULAR REFERENCE TO THE BENUE RIVER REGION, NIGERIA - Abubakar Alkali Fari; Adamu Sani Buba; Zulkanain Abdul Rahman (SEJARAH: Journal of the Department of History, 2025)
ABSTRACT The British made several attempts to explore the West African interior between 1788-1841. These explorations were driven by their desire to expand their colonial power and acquire new resources. One of the most notable and unsuccessful attempts was led by renowned explorer Mungo Park in (1795). He embarked on a journey along the Gambia River and reached the River Niger, but unfortunately died during the trip. Another attempt was made by Hugh Clapperton in 1825, who explored the Sokoto Caliphate and reached the coast of Lake Chad. However, he was also met with several challenges and had to turn back. In 1830, Richard Lander was able to successfully navigate the entire length of the River Niger, providing valuable insights into the region’s geography and potential for trade. Despite facing numerous obstacles, these British explorers played a significant role in expanding knowledge and influence in the West African interior. The paper draws on a variety of content analysis of documents which are narrative in nature and obtained substantially from secondary sources. primary and secondary sources, including official reports, travel accounts, and historical documents. The study concludes with a critical evaluation of the impact of British exploration on the West African Interior and its lasting effects on the region. Overall, this work contributes to new knowledge and a better understanding of the British presence in West Africa, particularly the Benue River of the Nigerian region, during the late 18th and early part of the 19th centuries.